New endoscopic classification of the cardiac orifice in esophageal achalasia: Champagne glass sign. Issue 6 (21st April 2016) - Gomi, Kuniyo; Inoue, Haruhiro; Ikeda, Haruo; Bechara, Robert; Sato, Chiaki; Ito, Hiroaki; Onimaru, Manabu; Kitamura, Yohei; Suzuki, Michitaka; Nakamura, Jun; Hata, Yoshitaka; Maruyama, Shota; et al.
Abstract : Background and Aim: Endoscopy, barium esophagram and manometry are used in the diagnosis of achalasia. In the case of early achalasia, characteristic endoscopic findings are difficult to recognize. As a result, the diagnosis of achalasia is often made several years after symptom onset. Therefore, we examined the endoscopic findings of the cardiac orifice in achalasia and propose a new classification. Methods: A total of 400 patients with spastic esophageal motility disorders who underwent peroral endoscopic myotomy (POEM) at our hospital between March 2014 and August 2015 were screened for this study. Champagne glass sign (CG) was defined as when the distal end of the lower esophageal sphincter relaxation failure (LESRF) was proximal to the squamocolumnar junction (SCJ) and the SCJ was dilated in the retroflex view. Specifically, CG‐1 was defined as a distance from the SCJ to the lower end of LESRF of <1 cm, and CG‐2 was defined as a distance ≥1 cm. Results: CG‐0 was seen in 73 patients (28.0%), whereas the CG sign was seen in 186 patients (71.3%), of whom 170 (65.1%) were CG‐1 and 16 (6.1%) were CG‐2. Conclusions: The CG sign is often observed in esophageal achalasia patients. CG‐0 (equal to Maki‐tsuki ) was observed in 28.0% of achalasia patients only. Its absence with dilated SCJ cannot be used to rule out achalasia. Barium esophagram and manometry should be done if esophageal achalasia is strongly suspected.